2013
DOI: 10.6002/ect.2012.0094
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic Acid Pharmacokinetics Early After Kidney Transplant

Abstract: Objectives: To determine the mycophenolic acid pharmacokinetic profile early after transplant in Iranian kidney graft recipients. Materials and Methods: A cross-sectional study was performed during 6 months in 31 patients who recently had kidney transplant and received fixed doses of mycophenolate mofetil (2 g/d). The plasma levels of mycophenolic acid were determined by high performance liquid chromatography. Results: The mean first mycophenolic acid peak level was 10 ± 5 mg/L. The mean mycophenolic acid area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In Thai kidney transplant recipients, MPA concentration at 2 hours had the highest correlation with MPA-AUC (r = 0.622); the time of the study was 4 months (19). In the study of Honarbakhsh et al (20), the recipients showed one peak, two peaks, or three peaks, and the time of the study was days 9 or 10. These differences depended on many factors including race, immunosuppression protocol, time from transplant, or MMF dosage.…”
Section: Discussionmentioning
confidence: 92%
“…In Thai kidney transplant recipients, MPA concentration at 2 hours had the highest correlation with MPA-AUC (r = 0.622); the time of the study was 4 months (19). In the study of Honarbakhsh et al (20), the recipients showed one peak, two peaks, or three peaks, and the time of the study was days 9 or 10. These differences depended on many factors including race, immunosuppression protocol, time from transplant, or MMF dosage.…”
Section: Discussionmentioning
confidence: 92%